Influence of Deviatoric Stress on the Deformation and Damage Evolution of Surrounding Rock under Unloading Conditions - Gongyu Hou; Jinping Liang; Haoyong Jing; Jinxin Tan; Yongkang Zhang; Xi Yang; Xin Xie (Shock and Vibration)
The study of the deformation and damage evolution behaviour of surrounding rock under excavation unloading conditions is of vital importance for a deep understanding of the mechanism of roadway failure. In this study, unloading testing using a partially hollow thick-walled cylinder cement mortar specimen with dimensions of 280 mm (height) × 200 mm (outer diameter) × 60 mm (inner diameter) and a solid height of 60 mm at the bottom was performed to investigate the deformation response and damage failure evolution characteristics of the surrounding rock. The experimental results showed that the higher deviatoric stress level accelerated the damage development caused by the unloading effect and improved the expansion rate of the internal cracks, which led to a higher radial strain rate, total strain, and acoustic emission hits. When deviatoric stress increased to a relatively higher level, the radial strain rates were highly unstable, and the surrounding rock near or at the opening free surface was damaged locally and regionally. During the failure process of the specimen, the generation of the deformation and damage in the unloading stage was more alive (as indicated by the growth rate). Nevertheless, the main deformation and damage to the surrounding rock were generated and accumulated in the maintaining stage after unloading.